Articulation Disorders in 5 Year Old Children at Assisi Medan Kindergarten - Br Bangun, Chamelia Tasri; Theresia, Rachel; Febrina, Mey (Indonesian Journal of Educational Science and Technology, 2024)
Articulation disorder is a common condition where your child is unable to produce certain sounds. For example, they always replace “r” with “w” or “th” with “s.” This disorder is not related to any problems with the brain, mouth or hearing. This research was carried out to look at the articulation problems of a 5 year old child at the ASISI MEDAN kindergarten. The researcher used qualitative methods with observation and interviews, the research involved 1 child and 1 teacher. Data collection was carried out by observing schools directly and interviewing teachers directly and using documentation methods to maximize research results. The stages in the analysis are namely data from the child, presenting the data and finally the conclusion of the research results.